3D modeling from radiograph with Conebeam geometry - Kawikitwitcha, S.; Pintavirooj, C.; Tosranon, P.; Kiriratnikbm, T.; Anuntaseree, S. (My University, 2004)
In order to render 3D model of the bone, the stack of cross-sectional images must be reconstructed from a series of X-ray radiographs, served as the projections. In the case where the distance between x-ray source and detector is not infinite, image reconstruction from projection based on parallel-beam geometry provides an error in the cross-sectional image. In such case, image reconstruction from projection based on conebeam geometry must be exercised instead. In this paper, the Simultaneous Algebraic Reconstruction Technique (SART Conebeam) is engaged for reconstructing tomograms in case of limited views of radiographs. Compared with Feldkamp Conebeam technique, the SART Conebeam theoretically gives the better quality of image for the same limited set of projections Volume rendering technique together with the shading effects is performed on a stack of cross-sectional image to realize the data into 3D visualization. The algorithms are applied to the practical situation where a series of x-ray radiographs of human femur bone are collected from a C-Arm x-ray apparatus. The 3D modeling of such bone is performed on the cross-sectional images reconstructed with SART conebeam. The results are very satisfactory. © 2004IEEE.
Keywords: Backprojection; Image Reconstruction; Radiograph; SART; Volume Rendering